2011
DOI: 10.1007/s10955-011-0299-3
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Classical Water Models at Interfaces and in Bulk

Abstract: Using concepts from perturbation and local molecular field theories of liquids we divide the potential of the SPC/E water model into short and long ranged parts. The short ranged parts define a minimal reference network model that captures very well the structure of the local hydrogen bond network in bulk water while ignoring effects of the remaining long ranged interactions. This deconstruction can provide insight into the different roles that the local hydrogen bond network, dispersion forces, and long range… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(121 citation statements)
references
References 44 publications
10
111
0
Order By: Relevance
“…2B. The Gibbs free energies of solvation, Ĝ, for the repulsive solutes in the WCA system scale with solute volume for all sizes, whereas solvation in the full LJ system displays a cross-over from scaling with solute volume to solute surface area at R HS ≈ σ LJ , consistent with the appearance of interfacial drying (13,14,27,28). The LMF prediction from Eq.…”
Section: Length Scale Dependence Of Solvophobic Solvationmentioning
confidence: 66%
See 2 more Smart Citations
“…2B. The Gibbs free energies of solvation, Ĝ, for the repulsive solutes in the WCA system scale with solute volume for all sizes, whereas solvation in the full LJ system displays a cross-over from scaling with solute volume to solute surface area at R HS ≈ σ LJ , consistent with the appearance of interfacial drying (13,14,27,28). The LMF prediction from Eq.…”
Section: Length Scale Dependence Of Solvophobic Solvationmentioning
confidence: 66%
“…Water was described using the SPC/E model, which adequately captures properties relevant to the description of hydrophobic hydration, including the isothermal compressibility and surface tension of water. Simulations of the SPC/E model were performed at T = 300 K and P = 0 atm, and the pressure in the GT system was appropriately corrected to yield the same density as the full system (28,31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously suggested that the closer approach of the larger ions to air-liquid interfaces could be the outcome of the actions of a repulsive (toward the interface) force, f rep , a net attractive force, f atr , due the unbalanced dispersive forces exerted by the whole liquid on interfacial layers, i.e., those accounting for macroscopic liquid cohesion (see Appendix S2 in the supplementary material 67 ), 11,[39][40][41] and the negative entropy of mixing associated with the creation of interfacial concentration gradients. The essential point for present purposes is that anion concentration profiles should peak at different depths, z = 1 − δ, depending on their ionic radii.…”
Section: Resultsmentioning
confidence: 99%
“…21 It has become apparent that the specificity and range of SIE cannot be explained by merely appending many-body electrodynamic (dipolar and dispersive) forces to electrostatics, as assumed by the classical DLVO (Derjaguin-Landau-Verwey-Overbeek) theory of surface interactions. 4,[23][24][25][26][27] The full consequences of quantum fluctuations within extended dielectric media in the presence of charges are being investigated using molecular dynamics simulations, 28 and continuum non-local electrostatics models based on a dielectric function ε(r, r ) of both the local electric field and the long-range polarization of the surrounding medium. [29][30][31] A key parameter in models dealing with cooperative effects is the length of correlations, λ, in this case those induced a) Authors to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%